István Hatvani – The Natural Philosopher: The Foundation and Application of Hatvani’s Natural Science Knowledge in Higher Education - POSTA, József (Studia Universitatis Babes-Bolyai Theologia Reformata Transylvanica, 2025)
During his theological and medical studies and doctoral work in Basel, Hatvani's goal was to acquire deeper mathematical knowledge. Therefore, from the second half of 1747, he attended the lectures of the world-famous mathematician Johann Bernoulli (1667–1748) and then of his son, Daniel Bernoulli (1700–1782). Hatvani studied in detail the posthumous work of Jakob Bernoulli (1654–1705), entitled The Art of Conjecture, published in 1713. Learning about the Bernoulli’s groundbreaking work helped him become the first in Hungary to teach probability and mathematical statistics and to perform real statistical calculations. In Leiden, Hatvani mostly attended lectures of physics and presentations of experiments by Pieter van Musschenbroek (1692–1761), who was a student of Newton. He listened to lectures delivered by the astronomer Johannes Lulofs (1711–1768) and the chemist Hieronymus David Gaubius (1705–1780). He gave his inaugural lecture at the Debrecen Reformed College in January 1749, bearing the title De matheseos utilitate in theologia ac in physica necessitate [On the Usefulness of Mathematics in Theology and Its Necessity in Physics]. Hatvani sets out from the assumption that mathematics is the most exact science of all. He acquired the most modern electrical equipment available at the time and used it to present physical experiments to his students. Making use of his chemical studies, Hatvani taught chemistry for the first time in Hungary starting from 1750. In 1777, he published a book on the analysis of the medicinal waters near Nagyvárad (Romanian: Oradea) and the examination of the salts in the vicinity of Debrecen. According to Hatvani, science and religion are independent forms of consciousness. In his eyes, they are equivalent forms of consciousness that presuppose each other in terms of the prosperity of humanity. Hatvani’s position is that he investigates first, then believes, and accepts as true only what he has carefully investigated. With this, he marked his own place on the road to theological rationalism.